SATISFACTION LEVEL OF PASSENGERS, SERVICE & FACILITY OF KMP DHARMA BAHARI SUMEKAR III BY IPA AND CSI METHODS - Kurnia Hadi Putra; Ita Suhermin Ingsih; Bambang Wahyudi (Journal Innovation of Civil Engineering (JICE), 2021)
Transport intends to ease the movement from one place to another. KMP Dharma Bahari Sumekar III belongs to one of transport facilities operated at Kalianget Port in Sumenep.This research aimed at investigating the satisfaction level of passengers taking KMP Dharma Bahari Sumekar III by implementing the methods of Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The research result indicated several essential attributes i.e. Quadrant II (toilet cleanliness in KMP Dharma Bahari Sumekar III and facility convenience for passengers in KMP Dharma Bahari Sumekar III and Quadrant II (safety in KMP Dharma Bahari Sumekar III, cleanliness in KMP Dharma Bahari III, the ability of officer in KMP Dharma Bahari Sumekar III to respond fast the emergent problems and be responsible on the safety and cozines of passengers). Meanwhile, the result of CSI method obtained 71,47%.